Cleft-like indentations in myxomatous mitral valves by three-dimensional echocardiographic imaging. Issue 14 (2nd May 2015) - Mantovani, Francesca; Clavel, Marie-Annick; Vatury, Ori; Suri, Rakesh M; Mankad, Sunil V; Malouf, Joseph; Michelena, Hector I; Jain, Sonia; Badano, Luigi Paolo; Enriquez-Sarano, Maurice
Abstract : Objectives: Cleft-like indentations (CLI) are deep separations between scallops of the mitral posterior leaflet observed in myxomatous mitral valve disease (MMVD), but their diagnosis, mechanisms and implications are unknown. Using 3D transoesophageal echocardiography (3DTOC), we aimed at assessing diagnostic accuracy and defining mechanisms of CLI in patients undergoing surgery for MMVD. Methods: 3DTOC of mitral valve was acquired in 49 patients with MMVD and severe regurgitation prior to valve repair. Qualitative review compared 3DTOC diagnosis of CLI with surgical inspection. Mitral, annular and leaflet dimensions were quantified with dedicated software and compared between those with and without CLI. Results: Diagnosis of CLI was made by 3DTOC in 17 (35%) while none was identified by 2D and was confirmed in 15 (88%) by surgical inspection. Mechanistically, LV diameters and mitral regurgitant volume (RVol) were similar with and without CLI (p>0.49). Conversely, mitral annulus was smaller with CLI (anteroposterior diameter 42.2±7.1 vs 47.0±7.5 mm, p=0.04; circumference 133±16 vs 148±19 mm, p=0.009; area 1289±326 vs 1619±427 mm 2, p=0.008). Prolapse volume tended to be smaller with CLI (1.9±1.2 vs 4.0±4.3 mL, p=0.06) involving single posterior scallop at surgery (82% vs 44%, p=0.007) with smaller 3DTOC leaflet area (1574±409 vs 2019±652 mm 2, p=0.01). During valve repair, surgical closure of all surgically diagnosed CLI was required. Conclusions: Posterior leaflet CLI are frequent in MMVD, are identified by 3DTOC with high accuracy and require closure during valve repair. CLI are mechanistically not related to excess annular enlargement or excess prolapse. Conversely, CLI occur in the context of single scallop prolapse with tissue paucity causing excess separation of scallops. These 3DTOC data enhance diagnostic and mechanistic comprehension of the diversity of MMVD phenotypical presentation.